Measurement of the azimuthal correlation between the most forward jet and the scattered positron in deep-inelastic scattering at HERA - Aaron, Francisc Dionisie; Hennekemper, Eva; Krüger, Katja; Lendermann, Victor; Pirumov, Hayk; Sauter, Michel David; Schöning, André; Schultz-Coulon, Hans-Christian (The European physical journal. C, Particles and fields, 2012)
Deep-inelastic positron-proton scattering events at low photon virtuality, Q 2, with a forward jet, produced at small angles with respect to the proton beam, are measured with the H1 detector at HERA. A subsample of events with an additional jet in the central region is also studied. For both samples, differential cross sections and normalised distributions are measured as a function of the azimuthal angle difference, Δϕ, between the forward jet and the scattered positron in bins of the rapidity distance, Y, between them. The data are compared to predictions of Monte Carlo generators based on different evolution approaches as well as to next-to-leading order calculations in order to test the sensitivity to QCD evolution mechanisms.
Gesehen am 08.11.2018